THE USE OF NEURAL NETWORK TECHNOLOGIES IN RESEARCH COMPETENCE FORMATION OF IT-SPECIALISTS FOR THE RAILWAY INDUSTRY IN MULTILEVEL TRAINING SYSTEM - Бондарева, Валентина; Мирошниченко, Ирина; Пахомова, Виктория; Скабалланович, Татьяна (SWorldJournal, 2020)
The article considers the development of formation methods of research competence with the use of neural network technologies of IT specialists for the railway industry in multilevel training system. The proposed method «ResCompStageNNT» consists of the f